PEMERTAHANAN BAHASA MADURA PADA KOMUNITAS “AL-BANJARI AS-SHOFA” DESA MASARAN KECAMATAN BLUTO KABUPATEN SUMENEP - Maulida Putri Amelia; Faiqotul Hasanah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Al-Banjari is a type of Islamic musical art that combines the singing of sholawat or praises for the Prophet Muhammad SAW with the rebana and other traditional musical instruments. The language used by the Al-Banjari community is Indonesian and Arabic, but we often hear some people using regional languages, specifically Madurese, during events such as religious gatherings, weddings, and so on. The factors contributing to the phenomenon of decreasing use of the Madurese language among the younger generation are: 1) young people prefer to use Indonesian in daily conversations, 2) many Madurese families who work or migrate to other cities are starting to abandon the Madurese language, 3) parents no longer use the Madurese language when communicating with their children, 4) young people are more interested in foreign languages than their own regional language, 5) lack of knowledge and understanding about the Madurese language. The type of research used is descriptive qualitative with a sociolinguistic approach. this association plays a significant role in fostering a love for language identity among young people.